2023
DOI: 10.1111/ijd.16710
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic predictors of melanoma in small diameter melanocytic lesions (mini‐melanoma): a retrospective multicentric study of 269 cases

Abstract: Background Incidence of cutaneous melanoma is steadily growing, and its early recognition is of paramount importance. Small, pigmented lesions often represent a challenge for the clinician, as predictors of melanoma have not yet been uniquely identified in this setting. Objectives To identify dermoscopic features that aid in distinguishing small diameter melanomas (≤5 mm) from equivocal melanocytic nevi measuring ≤5 mm. Methods A retrospective multicenter study was conducted to collect demographics, clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…These dermoscopic features play a significant role in the evaluation of SDMs. Interestingly, Nazzaro et al [ 14 ] observed atypical vessels exclusively in invasive melanomas with a diameter of ≤5 mm, although the association did not achieve statistical significance. Similarly, Regio Pereira et al [ 10 ] reported an association between atypical vascular patterns, macular blue-whitish areas, and shiny white structures with invasive small-diameter melanomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These dermoscopic features play a significant role in the evaluation of SDMs. Interestingly, Nazzaro et al [ 14 ] observed atypical vessels exclusively in invasive melanomas with a diameter of ≤5 mm, although the association did not achieve statistical significance. Similarly, Regio Pereira et al [ 10 ] reported an association between atypical vascular patterns, macular blue-whitish areas, and shiny white structures with invasive small-diameter melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicenter retrospective study [ 14 ], comprising 269 cases, including 103 SDMs (≤5 mm, flat, non-facial), 81 common melanocytic nevi (≤5 mm), and 85 control large (>5 mm) melanomas, demographics, clinical, and dermoscopic features were evaluated. The study found that SDMs were associated with a younger age at diagnosis and a preference for upper limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Nazzaro et al, the blue-white veil was a dermoscopic feature associated with the diagnosis of mini-melanomas with diameters ≤5 mm compared to clinically equivocal melanocytic nevi with diameters ≤5 mm. Also, they reported that the blue-white veil was detected more frequently in invasive mini-melanomas compared to in situ mini-melanomas [ 38 ]. In addition, reflectance confocal microscopy has recognized plump cells corresponding to melanophages and inflammatory infiltrates in histology within the blue areas recognized by dermoscopy [ 36 ].…”
Section: Dermoscopic Findings Of Pigmented Lesions After Laser or Ipl...mentioning
confidence: 99%
“…While most of the patients get a small scar after a wide excision, with almost zero morbidity, the negative emotional and economic effects of overdiagnosis support the efforts to reduce it ( 12 , 13 ). Nazzaro et al proposed five dermoscopic predictors of small diameter melanoma to decrease the rate of overdiagnosis and the unnecessary biopsies, but further research on larger datasets is needed to validate the results ( 14 ).…”
Section: Introductionmentioning
confidence: 99%